Oropharyngeal Probiotic ENT-K12 Prevents Respiratory Tract Infections Among Frontline Medical Staff Fighting Against COVID-19: A Pilot Study - Wang, Qiang; Lin, Xuan; Xiang, Xiaochen; Liu, Wanxin; Fang, Ying; Chen, Haiping; Tang, Fang; Guo, Hongyan; Chen, Di; Hu, Xiafen; Wu, Qingming; Zhu, Baoli; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Healthcare workers at the frontline are facing a substantial risk of respiratory tract infection during the COVID-19 outbreak due to an extremely stressful work schedule and public health event. A well-established first-line defense on oropharyngeal microbiome could be a promising strategy to protect individuals from respiratory tract infections including COVID-19. The most thoroughly studied oropharyngeal probiotic product which creates a stable upper respiratory tract microbiota capable of preventing upper respiratory tract infections was chosen to evaluate the safety and efficacy on reducing episodes of upper respiratory tract infections for COVID-19 healthcare workers. To our knowledge to date, this is the very first study describing the beneficial effects of oropharyngeal probiotic been administered by healthcare workers during the COVID-19 pandemic. In this randomized controlled trial, we provided the probiotics to frontline medical staff who work in the hospitals in Wuhan and had been in close contact with hospitalized COVID-19 patients for prophylactic use on a daily basis. Our finding suggests that oropharyngeal probiotic administration significantly reduced the incidence of respiratory tract infections by 64.8%, reduced the time experiencing respiratory tract infections and oral ulcer symptoms by 78%, shortened the days absent from work by 95.5%, and reduced the time under medication where there is no record of antibiotic and anti-viral drug intake in the probiotic group. Furthermore, medical staff treated with Bactoblis experienced sustained protection from respiratory tract infections since the 10th day of oropharyngeal probiotic administration resulting in an extremely low incidence rate of respiratory tract infections.